The Social Life of Former Convicts: (Social Adaptation in Society for Former Convicts Under Founding of Rehabilitation Center Class II City of Tanjungpinang) - Miswanto; Iswandi (Prodi Sosiologi Agama, 2018)
It’s hard for former convicts to get their place back in society, so they must adapt to society to get back to a normal life with others. But they are ostracized indeed by society. The readiness to do social adaptation is very difficult because former convicts always feel ostracized by society, moreover, they feel isolated in social interaction with others where they are living in. The goal of this research is to know how social adaptation in society for former convicts under the founding of the Rehabilitation Center Class II City of Tanjungpinang. The method of this research is descriptive qualitative which gives a full view of the phenomenon of what is happening in the field. The population of this research is 22 people, which uses purposive sampling to get 9 people as the sample, consisting of an informant and a key informant. Data collection by observation, interview, and documentation, will be analyzed by using data analysis from Mattew B. Milles and A. Michael Huberman. Former convicts who have finished their time of imprisonment and have to go back to society must adapt to a life with new regulations and they must know how to react if there are social problems that happen. Former convicts will be acceptable in society depending on their ability to adapt to others. It also happens to former convicts who have to go back to society with social status as ex-prisoner and they have to change their point of view of society to them. Former convicts have to show off their positive attitudes by doing better, being polite, diligent in praying, and not being unwilling to help society.